- #1

- 1,728

- 13

Shouldn't ##\frac{dp}{dE} = \frac{E}{p}## given that ##p = \sqrt{E^2 - m^2}##. Then the relation should be instead:

[tex]\frac{dp}{dE} = \frac{E}{p} = \frac{E}{\sqrt{E^2 - m^2}}[/tex]

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter unscientific
- Start date

- #1

- 1,728

- 13

Shouldn't ##\frac{dp}{dE} = \frac{E}{p}## given that ##p = \sqrt{E^2 - m^2}##. Then the relation should be instead:

[tex]\frac{dp}{dE} = \frac{E}{p} = \frac{E}{\sqrt{E^2 - m^2}}[/tex]

- #2

- 470

- 58

- #3

- 1,728

- 13

And I suppose ##c=1##?

- #4

- 470

- 58

Exactly.

Share:

- Replies
- 0

- Views
- 3K